2022
DOI: 10.1016/j.redox.2022.102245
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to H2O2-induced oxidative stress in human cells of different phenotypes

Abstract: Application of genetically encoded biosensors of redox-active compounds promotes the elaboration of new methods for investigation of intracellular redox activities. Previously, we have developed a method to measure quantitatively the intracellular concentration of hydrogen peroxide (H 2 O 2 ) in living cells using genetically encoded biosensor HyPer. In the present study, we refined the method and applied it for comparing the antioxidant system potency in human cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…It is established that the direct application of H 2 O 2 in cellular models is followed by the generation of oxygen (O 2 ) in the cells due to the cellular catalase activity and, as a consequence, free radicals are generated not only from the applied hydrogen peroxide but also from the released oxygen as well. While the exogenous H 2 O 2 has limited penetration within the cells and in normal cells, the extracellular-to-intracellular gradient can amount to thousands of times, , and the oxygen released in the cells due to the catalase action would be mainly responsible for the accumulation of free radicals and reactive oxygen species and the induced oxidative stress. In order to explain the requirement of a high concentration of H 2 O 2 to be applied for damages to be detected in the experimental models, an interesting recent study demonstrated that cells exposed to H 2 O 2 were able to convert it into O 2 in time as short as few minutes, meaning that the exposure to H 2 O 2 itself is in fact much shorter and less intense than initially considered.…”
Section: Resultsmentioning
confidence: 99%
“…It is established that the direct application of H 2 O 2 in cellular models is followed by the generation of oxygen (O 2 ) in the cells due to the cellular catalase activity and, as a consequence, free radicals are generated not only from the applied hydrogen peroxide but also from the released oxygen as well. While the exogenous H 2 O 2 has limited penetration within the cells and in normal cells, the extracellular-to-intracellular gradient can amount to thousands of times, , and the oxygen released in the cells due to the catalase action would be mainly responsible for the accumulation of free radicals and reactive oxygen species and the induced oxidative stress. In order to explain the requirement of a high concentration of H 2 O 2 to be applied for damages to be detected in the experimental models, an interesting recent study demonstrated that cells exposed to H 2 O 2 were able to convert it into O 2 in time as short as few minutes, meaning that the exposure to H 2 O 2 itself is in fact much shorter and less intense than initially considered.…”
Section: Resultsmentioning
confidence: 99%
“…Because hTrx-73VtK was the variant with the strongest multimerization bands, we next explored the effect of cellular reactive oxygen species (ROS) on its monomer–dimer–trimer equilibrium. Both rotenone and H 2 O 2 are well documented to increase cellular ROS production. , They would thus be expected to increase VtK-O levels and promote hTrx multimerization. However, the addition of up to 0.2 mM rotenone and 1 mM H 2 O 2 actually reduced the production of all forms of hTrx-73VtK (Figure b), possibly due to their interference with cell viability (Supplementary Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…Both rotenone and H 2 O 2 are well documented to increase cellular ROS production. 36,37 They would thus be expected to increase VtK-O levels and promote hTrx multimerization. However, the addition of up to 0.2 mM rotenone and 1 mM H 2 O 2 actually reduced the production of all forms of hTrx-73VtK (Figure 5b), possibly due to their interference with cell viability (Supplementary Figure 9).…”
Section: ■ Introductionmentioning
confidence: 99%
“…As hydrogen peroxide (H 2 O 2 ) was a product of the cellular oxygen metabolism that was a feature of the various metabolic and signaling cascades [ 12 , 32 ], the control of the physiological H 2 O 2 intracellular concentration, as an antioxidant indicator, has a significant relationship to the cells’ functionality and viability [ 33 ]. Therefore, the potential antioxidant activity of PKLPs on the cellular H 2 O 2 -induced oxidation model was established.…”
Section: Resultsmentioning
confidence: 99%